(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2026)
This research aims to find out whether the Duolingo Application can improve the vocabulary of the students, especially in verbs in 12th grade of MAN 1 Mamuju. The researcher applied a pre-experimental method by using one group pre-test and post-test design and collected data by giving pre-test and post-test. The result shows the improvement of students’ vocabulary by using the Duolingo application in 12th grade of MAN 1 Mamuju was good, because before using the Duolingo application the average score of students was 41.28. After the students used the Duolingo application, the average score of students increased to 73.52. This significant improvement occurred because the Duolingo application had a good effect in improving vocabulary, they are more enjoyable to learn, the application makes the students understand the material, and students can also learn vocabulary anytime and anywhere, so they do not get bored learning. Based on these results, it is recommended to use the Duolingo application to improve students’ vocabulary, especially in verbs.